Inversely Finding Peculiar Reaction Conditions toward Microfluidic Droplet Synthesis - Takashiro Akitsu (Reactions, 2023)
With the development of microfluidics, there are increasing reports of syntheses using not only conventional laminar flow at the microscale, but also the dissociation and aggregation of microdroplets. It is known, to some extent, that the microfluidics scale differs from normal scales in terms of the specific surface area, mass diffusion, and heat conduction; these are opposite to those in scale-up in-plant chemical engineering. However, it is not easy to determine what changes when the microdroplet flows through the channel. In this context, the author would like to clarify how the behavior of chemical species, which is expected to appear unique at the nanoscale, contributes to chemical reactions. What do we need in order to develop a completely new theory of chemical reactions? The characteristics of chemical reactions on the nanoscale are clarified via the encountering of solutions by the microfluidic device itself, or the chemical reaction of nanoscale droplets generated by the microfluidic device. Specifically, in recent years, experimental reports have accumulated that are expected to develop a fluidic device that can stably generate nanodroplets, and complex reactions of different reactivity are expected to occur that are specific to the nanoscale. In this short article, microfluidic devices, nanoscale droplets, experimental synthetic examples, and findings that may provide solutions are described.